Hubungan Antara Dukungan Sosial Keluarga dengan Motivasi Belajar Peserta Didik Dalam Mengikuti Program Kesetaraan Paket C di SKB Mojoagung - Binta Khuzaimah; Wiwin Yulianingsih (J+PLUS UNESA, 2023)
This research is motivated by problems regarding learning motivation in students when participating in the senior highschool equivalency program, which indicates a lack of motivation to learn. There are factors that influence learning motivation, one of which is extrinsic factors, namely family social support. The purpose of this study was to determine the significance of the relationship between family social support and students learning motivation in participating in the senior highschool equivalency program at SKB Mojoagung. This study uses a quantitative approach with a correlational research type. The data collection techniques used in this study were questionnaires and documentation with research respondents as many as 35 students of the senior highschool equivalency program at SKB Mojoagung. While the data analysis technique in this study uses the Product Moment formula to analyze the questionnaire. The results showed that family social support had a positive and significant relationship with the learning motivation of senior highschool equivalency students at SKB Mojoagung, as indicated by r count> r table (0.741>0.334) with a sig value = 0.000 <0.05. So that the higher the value of family social support, the higher the value of learning motivation, or conversely